Targeted disruption of the interferon-γ receptor 2 gene results in severe immune defects in mice - Lu, Binfeng (The National Academy of Sciences, 1998)
To study the role of the interferon- (IFN) γR2 chain in IFN-γ signaling and immune function, IFN-γR2-deficient mice have been generated and characterized. Cells derived from IFN-γR2 −/− mice are unable to activate either JAK/STAT signaling proteins or gene transcription in response to IFN-γ. The lack of IFN-γ responsiveness alters IFN-γ-induced Ig class switching by B cells from these mice. In vitro cultures of T cells demonstrate that the T cells from the IFN-γR2 −/− mice have a defect in Th1 cell differentiation. The IFN-γR2 (−/−) mice also produce lower amounts of IFN-γ in response to antigenic challenge. In addition, IFN-γR2 −/− mice are defective in contact hypersensitivity and are highly susceptible to infection by Listeria monocytogenes. These results demonstrate that the IFN-γR2 is essential for IFN-γ-mediated immune responses in vivo.